The Theosophical Society as a Pioneering Spiritual Enterprise: The Market and the Mahatmas - Rudbøg, Tim (Implicit Religion, 2024)
The Theosophical Society became one of the first both open and global occult organizations. Supported only by small membership fees and donations, it nevertheless became a success, establishing headquarters in India and local lodges around the world. After the first schism in the 1890s, the separate organizations equally thrived for a while. Due to the initial success, the Theosophical Society influenced the wider culture, setting an early standard for “occulture,” the pop-cultural devotion to the occult, which is now a billion-dollar industry. Later, organizations would serve as links to an even wider and more innovative spread of theosophical ideas, such as the idea of the mahatmas. This wider popularization would eventually lead to numerous products related to the mahatmas and to an emergence of new businesses demonstrating how already established market structures have been instrumental for the propagation of Theosophical ideas beyond the Theosophical Society.